Correction: Exploring the feasibility and conduction mechanisms of P-type nitrogen-doped β-Ga2O3 with high hole mobility. Issue 19 (9th May 2022) - Ma, Congcong; Wu, Zhengyuan; Jiang, Zhuoxun; Chen, Ying; Ruan, Wei; Zhang, Hao; Zhu, Heyuan; Zhang, Guoqi; Kang, Junyong; Zhang, Tong-Yi; Chu, Junhao; Fang, Zhilai
Abstract : Correction for 'Exploring the feasibility and conduction mechanisms of P-type nitrogen-doped β-Ga2 O3 with high hole mobility' by Congcong Ma et al., J. Mater. Chem. C, 2022, DOI: ; https://doi.org/10.1039/d1tc05324h .